2004
DOI: 10.1080/j.0001-6349.2004.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 expression in patients with uterine leiomyomas, uterine smooth muscle tumors of uncertain malignant potential (STUMP) and uterine leiomyosarcomas (LMS)

Abstract: Background:The aim of the current study was to evaluate the expression of Ki-67 in uterine smooth muscle tumors, comparing leiomyomas, uterine smooth muscle tumors of uncertain malignant potential (STUMP) and uterine leiomyosarcomas (LMS) and to prove the accuracy of a Ki-67 expression as a useful parameter in the diagnosis of LMS. Methods: Ki-67 was assessed using immunohistochemistry from paraffin-embedded tissue in 20 patients with uterine LMS, 22 cases of STUMP and 25 cases of leiomyomas. Results: Ki-67 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…In our series, positive Ki-67 staining was seen in 89% of CS cases, 67% of LMS cases, and 63% of ESS cases. Intense Ki-67 staining has been linked to malignant transformation [20,[24][25][26]. Accordingly, our results in CS and LMS cases are acceptable and in line with those of previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…In our series, positive Ki-67 staining was seen in 89% of CS cases, 67% of LMS cases, and 63% of ESS cases. Intense Ki-67 staining has been linked to malignant transformation [20,[24][25][26]. Accordingly, our results in CS and LMS cases are acceptable and in line with those of previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…13 In a study that evaluated Ki-67 expression, all of 22 STUMPs were, despite the presence of mitotic activity, Ki-67 negative and clinically benign. 18 Gokaslan et al reported similar findings in 2 STUMPs. 9 However, Ki-67 was positive in 8% and 35% of leiomyomas in each study, respectively.…”
Section: Discussionsupporting
confidence: 68%
“…have demonstrated a MIB1 proliferation index in excess of 15% in 93.5% of leiomyosarcomas, but in no STUMPs or cellular leiomyomas 18 . A low MIB1 proliferation index in STUMPs has also been found by Mayerhofer et al ., 29 in spite of considerable mitotic activity. In our study, all of the non‐sarcomatous lesions, except one usual leiomyoma, exhibited a MIB1 proliferation index of < 20%, while in 19 of 22 leiomyosarcomas this was in excess of 20%.…”
Section: Discussionmentioning
confidence: 70%